2006
DOI: 10.1002/jbt.20110
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of androgen receptor antagonists in the rat fetal testis reveals few common gene targets

Abstract: The androgen receptor (AR) is expressed in the fetal testis; however, the role of AR in fetal testicular development is poorly understood. Disrupted AR activity and subsequent gene expression alterations may disturb developmental programming of the fetal testis and result in testicular abnormalities later in life. The present study was performed to examine global gene expression patterns in rat fetal testis following in utero exposure to various AR antagonists. Pregnant Sprague-Dawley rats were treated with fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…However, recent studies using the transgenic Tfm mouse model (109), gene expression profiling of androgenregulated transcripts in neonatal mice testis (117), and combinations of hormonal manipulations in neonatal rat (118) suggested that androgens/AR might play a role in Sertoli cell proliferation, especially during early postnatal testis development. Another study using gene expression profiling of AR antagonists in the fetal rat testis suggested that the fetal testis is not a major target for AR activity during this stage of testis development, and results indicated that there are no overt histology changes and no common set of gene targets among various treated groups and the control group (119).…”
Section: A S-ar ϫ/Y Micementioning
confidence: 97%
“…However, recent studies using the transgenic Tfm mouse model (109), gene expression profiling of androgenregulated transcripts in neonatal mice testis (117), and combinations of hormonal manipulations in neonatal rat (118) suggested that androgens/AR might play a role in Sertoli cell proliferation, especially during early postnatal testis development. Another study using gene expression profiling of AR antagonists in the fetal rat testis suggested that the fetal testis is not a major target for AR activity during this stage of testis development, and results indicated that there are no overt histology changes and no common set of gene targets among various treated groups and the control group (119).…”
Section: A S-ar ϫ/Y Micementioning
confidence: 97%
“…Corn oil (CO) is one of the most common vehicles used for water‐insoluble agents in toxicity studies. Although some biologic effects on animals of CO have been reported – for example, that CO and diet could influence the reproduction and the kidney in female Sprague–Dawley rats (Sato et al , ), promote azoxymethane‐induced colon cancer development (Wu et al , ) and enhance hepatic lipid peroxidation in rats (Fang and Lin, ) – CO is still widely used as the vehicle for water‐insoluble agents in drug development (Bradford et al , ; Guerra et al , ; Poon et al , ; Lai et al , ; Xu et al , ; Patel et al , ), including recent molecular‐level studies of water‐insoluble agent effect on animal gene expression (Jacobus et al , ; Joseph et al , ; Mu et al , ; Satterfield et al , ; Aragon et al , ). It had been reported that CO could regulate genes related to cholesterol or fatty acid metabolism, which were tested only in rat liver (Takashima et al , ).…”
Section: Introductionmentioning
confidence: 99%